Compassionate use of convalescent plasma for the management of severe pneumonia in critically ill COVID-19 patients-a single center experience, Kerala, India - Paul, Mobin; C. G., Priyanka; M. P., Sophy; Abraham, Latha; Venkitakrishnan, Rajesh; Jos, Renji; Varghese, Jaicob (International Journal of Research in Medical Sciences, 2021)
We assessed treatment effectiveness with convalescent plasma in critically ill COVID-19 pneumonia patients and their association with reduction in C reactive protein level as a sensitive inflammatory marker to the ongoing cytokine storm. Retrospective cohort study based on the detailed electronic medical chart review. The primary outcome was a clinical improvement on day 14, defined as the reduction in cytokine storm as demonstrated by a drop in acute phase reactant C reactive protein; de-escalation from the prior mode of oxygen delivery or not on mechanical ventilation in critically ill COVID-19 patients. C reactive protein was measured by using immunoturbidimetry. IgG antibody against spike protein S1 was measured by chemiluminescent immunoassay. Of 14 patients, all had severe COVID-19 pneumonia [category C], and 9 (64%) were mechanically ventilated soon after the admission into the medical intensive care unit. De-escalation of the oxygenation strategy mode was noted in 11 (79%) patients after convalescent plasma infusion. All patients showed a significant drop in C reactive protein when compared to pre-infusion and post-infusion day 5. Early compassionate use of convalescent plasma with higher titters of IgG antibodies against S1may positively benefit the overall outcome in critically ill COVID-19 patients with severe pneumonia.